Impact of Preoperative Prealbumin on Outcomes After Cardiac Surgery. (4th June 2014) - Yu, Pey‐Jen; Cassiere, Hugh A.; Dellis, Sophia L.; Manetta, Frank; Kohn, Nina; Hartman, Alan R.
Abstract : Background: Preoperative malnutrition is increasingly prevalent in patients undergoing cardiac surgery. Although prealbumin is a widely used indicator of nutrition status, its use in the preoperative assessment of patients undergoing cardiac surgery is not well defined. The purpose of this study is to determine the impact of preoperative prealbumin levels on outcomes after cardiac surgery. Materials and Methods : Data were prospectively gathered from February 2013 to July 2013 on 69 patients undergoing cardiac surgery. Prealbumin levels were obtained within 24 hours of surgery. Patients were divided into 2 groups based on a prealbumin cutoff value of 20 mg/dL. Results : Of the 69 patients, 32 (46.4%) had a preoperative prealbumin ≤20 mg/dL. There was no correlation between prealbumin levels and body mass index ( r = −0.13, P = .28). Likewise, there was no correlation between preoperative albumin and prealbumin levels ( r = 0.09, P = .44). Nine of 32 (28.1%) patients with low preoperative prealbumin levels had postoperative infections compared with 2 of 37 (5.4%) patients with high prealbumin levels ( P = .010). Patients with low prealbumin levels also had increased risk of postoperative intubation for >12 hours ( P = .010). Conclusions : Patients undergoing cardiac surgery with preoperative prealbumin levels of ≤20 mg/dL have an increased risk for postoperative infections and the need for longer mechanical ventilation. If feasible, nutrition optimization of such patients may be considered prior to cardiac surgery.